2015
DOI: 10.1021/acssuschemeng.5b00307
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Performances and Mechanisms of Amidoxime Resin toward Gallium(III) and Vanadium(V) from Bayer Liquor

Abstract: The adsorption of Ga­(III) and V­(V) onto an amidoxime resin (LSC700) has been investigated. The parameters studied include the effects of contact time, initial metal ions concentration, and temperature by batch method. The adsorption capacity of the resin for Ga­(III) and V­(V) was found to be 29.24 and 22.60 mg/g, respectively. The adsorption kinetics of Ga­(III) and V­(V) onto LSC700 could be well elucidated with Lagergren-second-order equation. The Langmuir isotherm fitted the experimental data well, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 28 publications
1
18
0
3
Order By: Relevance
“…Long et al [60] reported the appearance of a peak at 595 cm −1 after Ga(III) sorption on a resin bearing amidoxime groups and the weak impact of metal binding on nitrogen-based compounds: they concluded that Ga(III) sorption occurred on the O group of amidoxime group. Zhao et al [10] also reported for Ga(III) recovery from Bayer liquor using LSC-700 amidoxime-based resin that gallate ions (i.e., Ga(OH) 4 − ) are bound on deprotonated OH group of amidoxime moiety. The large band associated to silica does not allow identifying this peak on the PAN/SiO 2 sorbent; in addition Ga(III) was bound on the sorbent at pH close to 4, where Ga(III) is not present as gallate: the sorption mechanism is probably different.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Long et al [60] reported the appearance of a peak at 595 cm −1 after Ga(III) sorption on a resin bearing amidoxime groups and the weak impact of metal binding on nitrogen-based compounds: they concluded that Ga(III) sorption occurred on the O group of amidoxime group. Zhao et al [10] also reported for Ga(III) recovery from Bayer liquor using LSC-700 amidoxime-based resin that gallate ions (i.e., Ga(OH) 4 − ) are bound on deprotonated OH group of amidoxime moiety. The large band associated to silica does not allow identifying this peak on the PAN/SiO 2 sorbent; in addition Ga(III) was bound on the sorbent at pH close to 4, where Ga(III) is not present as gallate: the sorption mechanism is probably different.…”
Section: Tablementioning
confidence: 99%
“…The most conventional processes for the treatment of Bayer liquor include solvent extraction, electrochemical deposition, fractional precipitation and ion exchange. However, many of these technologies have important drawbacks that hinder their application [10]. For example, the electrochemical deposition method was banned in most countries because of the high toxicity of mercury [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of Al 2 O 3 leaching bauxite, Ga, vanadium (V), magnesium (Mg), silicon (Si), and calcium (Ca) are leached into Bayer liquor together with Al (aluminum) 16 . Various methods were performed to purify Ga from Bayer liquor have been studied, 17 such as electrochemical method, stepwise precipitation method, solvent extraction method, and ion exchange resin adsorption method 18 . These methods incur some drawback such as low‐extraction rate, high cost, and environmental pollution that is why are being less practiced 19–22 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the method has been widely applied in industrial practice, especially in China (Aluminum Corporation of China Limited). Although most of Ga(III) was adsorbed successfully, a part of V(VI), Mg(II), Si(IV), Ca(II), and Al(III) was coextracted, by HCl eluted solution, which would harm electrolysis of high‐purity metal Ga 17 . TBP/SiO 2 ‐P as the secondary time adsorption material is an excellent material to recover Ga(III) from hydrochloric acid (HCl) solution efficiently, exhibited excellent selectivity toward Ga(III) and almost has no adsorption effect on other competitive ions, ultrapure water can quickly and effectively remove Ga(III) from resin.…”
Section: Introductionmentioning
confidence: 99%
“…Among all kinds of adsorption resins, the resins containing amidoxime groups have the best adsorption performance on gallium. Amidoxime group, that is, an oxime group (NOH) and an amino group (NH 2 ) connected to the same carbon atom, 19 can form the chelation with selectively extract metal ions, thereby achieving the purposes of separation, recovery, and purification 20 . Kataoka et al 21 first used amidoxime ion exchange resin to separate pure gallium from Bayer liquor, and the recovery efficiency was over 96%, while the aluminum adsorption amount was only 0.1%, showing efficient selectivity.…”
Section: Introductionmentioning
confidence: 99%